Increasing the Intention to Revisit Villa Kota Bunga Through Customer Satisfaction as an Intervening Variable - Andri Dwi Priyanto; Hari Muharam; Yuary Farradia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the role of customer satisfaction in mediating the influence of facilities and location on the intention to revisit Villa Kota Bunga. The research is expected to provide valuable input for the management of Villa Kota Bunga in improving its facilities, location, and customer satisfaction. The sampling method used was purposive and accidental sampling by distributing questionnaires to 200 domestic guests who are currently staying or have previously stayed at Villa Kota Bunga. The questionnaire data were processed using SPSS Version 25 and Lisrel 8.80 software. The results show that facilities and location have a positive effect on customer satisfaction, facilities and location positively influence the intention to revisit, and customer satisfaction is able to partially mediate the influence of both facilities and location on the intention to revisit Villa Kota Bunga.